THE INFLUENCE OF STRESS RELIEVING PARAMETERS ON THE PROPERTIES OF CLOSED-CELL ALUMINIUM ALLOY FOAM - PUSPITASARI, DEWI (2018)
Nowadays, the interest in metallic foam is increasing since their cellular structures have a unique combination of properties such as high stiffness, low density, lightweight, high specific strength and thermal insulation